Capital Flows: Issues and Policies - Peter Montiel (Inter-American Development Bank (IDB), 2013)
This paper presents an analytical overview of recent contributions to the literature on the policy implications of capital flows in emerging and developing countries, focusing specifically on capital inflows as well as on the links between inflows and subsequent capital-flow reversals. The objective is to clarify the policy challenges that such inflows pose and to evaluate the policy alternatives available to the recipient countries to cope with those challenges. A large menu of possible policy responses to large capital inflows is considered, and experience with the use of such policies is reviewed. A policy `decision tree`-i. e. , an algorithm for determining how to deploy policies in response to an exogenous inflow episode- is developed, and strategies to achieve resilience to both inflows and outflows in a world where exogenous events may frequently drive capital flows in both directions are discussed.
Keywords: F32; F34; F36; F62; 330